Accessing Government Eye Care Services: Expriences of Children With Eye Health Conditions in Mubende, Uganda - Odette Tumwesigye Niyisabwa; Elijah Musenyente (Journal of Health Promotion and Behavior, 2021)
Background: Apart from parents reluctance towards childrens early eye-care, government eye care services are costly, few ophthalmologists are in place, yet people suffering from eye infections are increasing. This study aimed to explore the response of parents towards exposing their children with eye health conditions to early eye care services, the efficiency of eye care services offered and the costs involved in accessing eye care services.Subjects and Method: This was a qualitative study with in-depth interview. Conducted in Mubende, Uganda, from June 2019 to May 2020. A total of 12 informants were selected by purposive sampling. The data were collected using semi structured interviews from 12 participants involving children with eye health conditions and one (1) ophthalmic Officer (OCO). Investigator triangulation method was used whereby each participant was interviewed by more than one investigator as a way of obtaining several differing opinions concerning issues in question. The transcribed data were analyzed using content analysis.Results: The findings indicated that, parental responsibility for children with eye health conditions for early assessment, diagnosis and treatment was generally lacking among fathers than among mothers. Poverty, illiteracy and ignorance among parents, use of traditional herbal treatment of eyes often resulted in serious consequences. Regarding efficiency, there were a lot of hardships in accessing the eye care services due to limited eye care centres, inadequate skilled or specialized personnel and irregular attendance by medical staff in government eye-care centres. The eye health care services were found to be expensive and unaffordable by the community.Conclusion: The study concluded that overall, opportunities for visual assessment, diagnosis and treatment for children with eye health conditions in Mubende District were generally limited. Comprehensive eye care services that covers every member of the community are highly recommended.Keywords: eye-care services, eye health conditions, Mubende-UgandaCorrespondence: Odette Tumwesigye Niyisabwa. Department of Community and Disability Studies, Kyambogo University. Kyambogo Road, Kampala, Uganda. Email: niyisabwa.odette@gmail.com. Mobile: +256772968235Journal of Health Promotion and Behavior (2021), 06(02): 121-132DOI: https://doi.org/10.26911/thejhpb.2021.06.02.05